Sosialisasi dan Sharing Session Pemanfaatan Plugin AI di Microsoft Excel dan Word untuk Administrasi Desa Sladi - Mahesa Rizky Saputra; Lazuardi Lazuardi; Nurul Karisma; Agil Ario Wibawa; Aghsyannisa Aghsyannisa; Siti Munawaroh; Syamsul Mu’arif; Siti Jamilah (Jurnal Kemitraan Masyarakat, 2025)
This community service activity was carried out in Sladi Village with the goal of improving the digital literacy of village officials through the utilization of Artificial Intelligence (AI) plugins in Microsoft Word and Excel. The main issue faced by the village officials was their limited ability to use digital technology, which resulted in administrative tasks being carried out manually and inefficiently. Therefore, this digital literacy training aimed to enhance the skills of village officials in utilizing digital tools, especially AI, to support their administrative work. The method used in this activity was Participatory Action Research (PAR), which involved the stages of diagnosing, action planning, action taking, evaluating, and specifying learning. Evaluation of the activity was conducted using Likert scale questionnaires and open-ended questions to collect feedback from participants regarding their understanding and responses to the training provided. Data analysis was carried out using SPSS to calculate the mean, standard deviation, and qualitative findings from the open-ended questions. The evaluation results showed that the benefits of the activity (mean = 4.2) and the intention to implement AI (mean = 4.2) received the highest scores, indicating that the participants found the training highly beneficial and were motivated to apply AI in their daily tasks. On the other hand, the understanding of AI in Excel (mean = 3.7) and the assessment of the material (mean = 3.7) showed that further in-depth learning was needed to improve participants' comprehension and skills. Overall, the activity successfully improved the skills of village officials and raised collective awareness to transition towards a more efficient and adaptive digital village administration. This training is expected to positively contribute to the digital transformation in the village.